Randomized Controlled Trial of Labetalol Versus Hydralazine, for Severe Hypertension in Obstetric Patients, at Tertiary Care Hospital of Karachi - Saima Aziz Siddiqui, Farah Shabih Ul Hasnain, Riffat Jaleel (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Blood pressure ≥160/110 mm Hg, is indication for urgent drug therapy in obstetric women, to prevent complications and deaths. There is limited data for comparison of Labetalol to Hydralazine in emergent treatment of severe pregnancy related hypertension. Methods: Randomized controlled trial, analyzed 184 women with severe hypertension at ≥28 weeks of pregnancy or within 72 hours after delivery, from October 2012 to September 2014. Ninety-two patients in each group received intravenous Labetalol or Hydralazine boluses, repeated every 10 or 20 minutes respectively (maximum 5 boluses). Outcome measures comprised blood pressure reduction <160/110 mm Hg, mean arterial pressure, severe persistent hypertension, number of boluses, maternal hypotension, tachycardia, adverse effect on fetal heart, still birth and neonatal bradycardia. Data was collected on a semi -structured proforma and analyzed through SPSS version 20. Numeric outcome measures were compared by Mann Whitney U test or independent sample t test according to normality distribution. Qualitative measures were compared by Chi square or Fisher’s exact test. Level of significance was <0.05 Results: There was no significant difference in reduction of systolic, diastolic blood pressure and severe persistent hypertension, between Labetalol and Hydralazine (p>0.05). Tachycardia, palpitation, headache, were significantly higher (p <0.05) in Hydralazine group. Adverse effects on fetal heart were not statistically significant. Numbers of boluses were significantly lower in labetalol group. Conclusion: Labetalol is equal to hydralazine in reducing severe pregnancy related hypertension. Maternal side effect profile of Labetalol is better, and it achieves blood pressure control with reduced boluses. Keywords: Pregnancy-induced hypertension, Hypertensive crisis, Labetalol, Hydralazine, Pregnancy, Preeclampsia, Antihypertensive agent.